What makes a change? Understanding the renewal process of barley cultivars on Finnish farms - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri (Elsevier BV, 2023)
The potential to adapt to climate change varies depending on the crop and is considered low especially for barley (Hordeum vulgare L.) in Europe. Barley is the most widely cultivated crop in Finland, grown in a wide range of climatic and edaphic conditions. Access to a large and diverse assortment of locally well adapted, climate-resilient barley cultivars is the premise for successful cultivation. Barley has plenty of cultivar choices in Finland. However, cultivar switch is “a hidden process,” and in this study, we therefore aimed: 1) to increase understanding of farmers’ cultivar renewal process; 2) to study how yield and growing time of new cultivars have changed when farmers switched cultivars; and 3) to describe how farms with willingness to change cultivars differ from those reluctant to make a change. The renewal interval of barley cultivars is long: The cultivars grown in 2018 were usually introduced to the Official Variety Trials as early as 2008–2012. The median age difference between replaced and new cultivars was seven years. The probability of switching cultivars was systematically higher on larger farms and farms with a large cereal area. New cultivars were allocated primarily to high-yielding field parcels owned by a farmer. Farmers aspired for an increased yield potential, but this did not necessarily entail a shift to later maturity. We found strong spatial dependency in cultivar renewal if the distance between the neighboring farms was < 5 km. The direction of the change was not only toward new breeds as long as the cultivar was high yielding. When returning to an older cultivar, it was likely that the new breed did not meet the farmer’s expectations, or that the growing season was exceptionally challenging.
Keywords: ohra; lajike; lajikkeen ikä; lajikkeen vaihto; kasvuaika; maanviljelijät; maatilat; Barley; Cultivar age; Cultivar change; Farm characteristic; Growing time; Spatial dependency; Yield